The Effect of Environmental Disclosure and Green Innovation on Firm Value: The Role of GCG - Nicko Albart; Hadi Purnomo (Lembaga Riset dan Inovasi Al-Matani, 2026)
This study examines the effect of environmental disclosure and green innovation on firm value, with Good Corporate Governance (GCG) serving as a moderating variable. Previous studies have reported inconsistent findings regarding the relationship between sustainability practices and firm value, indicating the need for further investigation, particularly in emerging market contexts. This study employs a quantitative approach using panel data obtained from property and real estate companies listed on the Indonesia Stock Exchange during the 2020–2024 period. The data were analyzed using panel data regression and Moderated Regression Analysis (MRA). The findings reveal that environmental disclosure negatively affects firm value, indicating that sustainability disclosure in emerging markets is not always perceived positively by investors. Green innovation does not significantly influence firm value, suggesting that environmentally oriented innovation activities have not yet been fully appreciated by the market. In contrast, Good Corporate Governance has a positive effect on firm value and strengthens the relationship between green innovation and firm value. However, GCG does not strengthen the relationship between environmental disclosure and firm value. The findings imply that strong governance mechanisms enhance the effectiveness and credibility of sustainability-oriented innovation strategies, thereby increasing investor confidence and market valuation. This study also indicates that environmental disclosure alone may not improve firm value unless supported by credible implementation and transparent governance practices. Therefore, companies are encouraged to integrate sustainability initiatives into long-term business strategies rather than relying solely on symbolic disclosures. Theoretically, this study contributes to legitimacy theory, signaling theory, stakeholder theory, and corporate governance theory by demonstrating that investor responses toward sustainability practices are influenced by governance quality and market perceptions in emerging economies. These findings contribute to the literature on sustainability, innovation, and corporate governance in developing-country contexts.